Can a stressed oncologist be good in a consultation? A qualitative study on the oncologists' perception. (13th April 2014) - Groß, S.E.; Ernstmann, N.; Jung, J.; Karbach, U.; Ansmann, L.; Gloede, T.D.; Pfaff, H.; Wirtz, M.; Baumann, W.; Schmitz, S.; Osburg, S.; Neumann, M.
<x xml:space="preserve">Abstract</x> The aim of this exploratory study was to examine how the working conditions and job stress of private practice oncologists (PPOs) affect their interaction with patients. Data for the study were collected through semi‐structured interviews with PPOs selected based on purposeful sampling criteria. The data were evaluated using content analysis. Factors perceived by PPOs to influence their level of stress and patient care were some of their own personal characteristics as well as working conditions both within and outside their practices. Apart from being able to name specific stressors (e.g. dysfunctional organisational workflow and interruptions during medical encounters), the oncologists also mentioned individual and organisational resources (e.g. professional experience, well‐educated nurses and good work organisation) for coping with job stress and improving interaction with patients. Within this study, we identified some obstacles on the individual and organisational level for good patient care, as working conditions which might lead to time pressure and stress, which subsequently have an impact on quality in patient care (e.g. less time for personal issues during patient consultations). Future stress research should conduct a more in‐depth investigation of these and other interventions at both the individual and organisational levels in order to improve patient care.